1985
DOI: 10.1002/mrc.1260230718
|View full text |Cite
|
Sign up to set email alerts
|

73Ge and 13C NMR spectra of some methylgermacyclohexanes

Abstract: RESULTS AND DISCUSSION73Ge is an esoteric nucleus as far as NMR spectroscopy is concerned, chiefly because of its large quadrupolar moment, which tends to cause excessive broadening of signals, and there are many fewer reported data than for other Group IVB elements.' So

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The 73 Ge NMR resonances (3), including those involved in the highest intensity absorption peak (HOMO and LUMOþ4). for 1,1-dimethyl-1-germacyclochexane, 1-methyl-germacyclohexane, and the germanium-unsubstituted germacyclohexane were observed at d À13.7, À65.3, and À131.2 ppm (respectively) [19].…”
Section: Resultsmentioning
confidence: 97%
“…The 73 Ge NMR resonances (3), including those involved in the highest intensity absorption peak (HOMO and LUMOþ4). for 1,1-dimethyl-1-germacyclochexane, 1-methyl-germacyclohexane, and the germanium-unsubstituted germacyclohexane were observed at d À13.7, À65.3, and À131.2 ppm (respectively) [19].…”
Section: Resultsmentioning
confidence: 97%
“…Takeuchi et al published a series of thirteen papers in the 1980s that focused on the 73 Ge NMR of numerous germanes and correlated their spectral data with those of the analogous silicon and tin compounds [48][49][50][60][61][62][63][64][65][66][67][68][69]. Molecular mechanics calculations were also used to further explain the experimental data.…”
Section: Isrn Spectroscopymentioning
confidence: 99%
“…The spectrum of the unsymmetrical compound Me 3 GeCH 2 CH 2 COOH was also acquired, and this compound exhibited a resonance at δ 6.3 ppm with a ν 1/2 value of 54 Hz, where the line broadening is result of the perturbation of the electric field gradient at the germanium center [60]. It was also shown that 73 Ge NMR, when combined with 13 C NMR, could be used to determine the conformation of organogermanium compounds [48]. The 73 Ge NMR spectrum of 1,4-dimethylgermacyclohexane exhibited two resonances at δ −61.5 and −73.4 ppm, where the resonance at δ −61.5 ppm is assigned to the trans-isomer while the other resonance corresponds to the cis-isomer (Scheme 1).…”
Section: Isrn Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations